Ambient temperature and sexual activity: Evidence from time use surveys - Tamás Hajdu; Gábor Hajdu (Hungarian Academy of Sciences, Institute of Economics, 2017)
Previous research has found that unusually hot temperature in a given month reduces birth rates 8-10 months later. We examine one of the potential mechanisms behind this relationship. Using three waves of the Hungarian Time Use Survey we analyze the relationship between ambient temperature and sexual activity. We show that on a cold day sexual activity is significantly lower, but hot temperatures do not have an effect. Performing placebo tests using temperature data one year ahead or several years before we provide evidence that supports the causal interpretation of our results. Studying the dynamics of this relationship, we could not rule out the possibility that after the immediate decline, sexual activity revives over the next few days resulting in a zero total effect.
Keywords: J13; J22; Q54; 330; weather; temperature; sexual activity; time use